Estrés académico en universitarios peruanos: importancia de las conductas de salud, características sociodemográficas y académicas - Cassaretto, Mónica (2021)
Background: While in college, students face specific situations that might be stressful. To recognize such experience, this research proposes the term academic stress, which causes symptoms that may affect students’ health. Objective: To describe the prevalence of academic stress and its components, and to analyze the role of sociodemographic, academic and behavioral variables in the dimensions of stress. Method: The study population accounted for 1,801 college students from six Peruvian cities, out of which 57.7% were women aged between 18 and 54 (M = 20.79, SD = 2.69). The SISCO Inventory of Academic Stress and the Lifestyle Questionnaire for Young College Students – Peru (CEVJU – Peru) were administered. Results: Eighty-three percent (83%) of the students indicated having experienced academic stress during the semester: mostly medium and medium-high stress levels. Multiple linear regression analyses conducted for each stress indicator showed median models for stress level (R2 = .16, p < .001) and frequency of stressors (R2 = .13, p < .001), and large models for symptoms (R2 = .32, p < .001). Health behaviors had a significant effect in all the models. Conclusions: Academic stress is a major problem for college students. There is evidence of the predictive role of sex, study motivation and most health behaviors in the academic stress indicators.